WORKS LIFE BALANCE GEN-Z: APPROACHING TECHNOLOGICAL CHANGE AND SOCIAL AWERENEES - Muh. Dedi Miswar; Herawaty; Alfian Maulana (PT. Jurnal Center Indonesia Publisher, 2025)
This research aims to determine the partial influence of technological changes and social awareness on the work-life balance of Gen Z in the city of Makassar. This research is associative research with a quantitative approach. The sample in this research consisted of 120 worker respondents in the city of Makassar and the data collection technique used in this research was a questionnaire and the data analysis technique used was multiple regression with SPSS software. The test results show that the technological change variable has a significant influence on Gen Z's work-life balance and social alertness has a significant positive influence on Gen Z's work-life balance.